Assessment of facial profile changes in patients treated with maxillary premolar extractions - Almeida-Pedrin,Renata Rodrigues de (2012)
OBJECTIVE: Evaluate the facial profile changes of orthodontic treatment with extraction of two upper first premolars, from the perspective of orthodontists, dentists and lay people. METHODS: Facial profiles of radiographs taken before and after treatment of 70 patients with Class II, division 1 malocclusion were traced. The silhouettes of the 70 patients were randomly assembled in an album with, being two profiles on each sheet of the same patient. Then, 30 orthodontists, 30 dentists and 30 lay people chose the more esthetic facial profile (A or B), and the amount of change they perceived between the two profiles before and after treatment, according to a visual analog scale (VAS). RESULTS: The results revealed that 83 examiners preferred the post-treatment profiles, and only three dentists and four lay people chose the profiles pre-treatment more frequently. Thus, the orthodontists often chose the profiles after treatment, followed by dentists, with no statistically significant differences found between dentists and lay people. There were significant differences within groups in the preference of pre- and post-treatment profile. Furthermore, the three groups of evaluators indicated that pre and post-treatment profiles did not differ substantially. CONCLUSIONS: The treatment of Class II, division 1 malocclusion with extraction of two first premolars has a positive effect on facial profile esthetics.